Network Relationships in Knowledge Intensive Business Services: Does it vary by Firm Age and Type - Sareen, Amit; Pandey, Dr. Sharadindu (The journal of contemporary issues in business and government, 2021)
Knowledge intensive business services (KIBS) are becoming a key pillar of the services economy particularly in the Indian context. Network relationships with external partners is an important source of information, knowledge and technology. Network partners include customers, suppliers, select competitors and investors. These network relationships may vary as a firm grows in terms of age or depending on the firm type. KIBS firms have been classified into different age bands: 1 to 10 years; 11 to 20 years; and 21 years or above. In terms of firm type, KIBS firms have been typically classified into technical KIBS or professional KIBS. The study evaluates how network relationships in KIBS firms vary by firm age and type. There is limited literature in this area and the study provided crucial insights to KIBS firm of different ages and types on how best to leverage their network relationships. The study involved cross-sectional survey across a wide spectrum of KIBS firms based in India with 151 valid responses from middle to senior level executives. The study finds that network relationship with suppliers of KIBS firms 21 years or above is stronger as compared to KIBS firms upto 10 years old. Also the network relationship with investors of technical KIBS is stronger as compared to professional KIBS.